Memberdayakan Pertahanan Indonesia: Evolusi Masyarakat Militer Cerdas dalam Sistem Perang Rakyat Semesta - Nugraha, Ridwan Akhmad; Sulistyadi, Edy; Suseto, Buddy (Policy and Maritime Review, 2024)
In the context of Indonesia's Total People’s War, the concept of a Smart Military Society emerges as a pivotal element in modern defense practices. This study aims to explore the integration of information technology, artificial intelligence, connectivity, and collaboration within military operations to construct an efficacious Smart Military Society. By harnessing the potential of ICT and smart technology, the Indonesian defense sector can effectively enhance situational awareness, decision-making processes, and response capabilities to address evolving threats. The collaboration with societal stakeholders, academia, and industries fosters innovation, adaptability, and the development of a technologically advanced defense industry. Through joint exercises and information sharing, the interoperability of defense forces improves, leading to coordinated efforts across different military components. Challenges such as cybersecurity measures must be addressed to safeguard sensitive information and critical infrastructure. The implementation of a Smart Military Society not only strengthens Indonesia's defense capabilities but also stimulates economic growth, promotes self-reliance, and enhances national security. This research contributes profound insights into the potential and challenges associated with Smart Military Society, offering valuable implications for adaptive defense strategies in the complexities of modern warfare.